Visits for alcohol-related problems in a large urban Emergency Department. Results of a 15-year survey. - Comelli, Ivan; Lippi, Giuseppe; Sanchis-Gomar, Fabian; Turcato, Gianni; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2018)
Alcohol abuse is associated with a high burden of morbidity and mortality. Nevertheless, definitive epidemiological data on alcohol-related visits in the emergency department (ED) is substantially lacking. This study was aimed to analyze the epidemiological patterns and temporal trends of alcohol-related visits in the local ED, and assessing the healthcare burden of cases needing hospital admission. All patients visited for alcohol-related problems between the years 2002-2016 were anonymously identified from the hospital database. All cases were classified according to the main cause leading to ED, age and gender, time of presentation, disposition. Overall, 8014 cases were identified (2249 women and 5765 men). Women were younger than men. The overall trend during the study period was characterized by a constant increase in the number of alcohol-related ED admissions. A significant number of subjects had multiple alcohol-related visits. A total number of 747 patients were visited twice, 259 three times and 107 four times. A mostly nocturnal pattern of ED presentation was observed in both genders, peaking between midnight and 2 AM, and an increased number of visits was recorded during the weekends. The vast majority of patients (64%) could be discharged within 6 hours, but a considerable number needed longer observation and treatment in the ED. Overall, 7551 patients were discharged from the ED, whilst 462 patients needed hospital admission, 179 for traumatic injuries and 283 for non-traumatic causes. The decreasing age of subjects admitted to the ED with alcohol-related problems should now be regarded as a public healthcare issue.